Albino animals - Halls, Kelly Milner, 1957- (Darby Creek Pub., 2004)
Everyone has probably seen the white mice or rabbits with pink eyes. Learn about these and other albino animals, the genetics that cause albinism, and the survival challenges albinos face. Have you ever seen an albino mouse or rabbit? What makes them albino? Albino animals carry a specific gene that makes their hair, their skin, and their eyes have no color. Albinos exist in virtually every species on earth-insects, birds, fish, and mammals-even humans. Each species is represented in the book, along with eye-catching photography.